The scaling of the density of states in systems with resonance states - Pont, Federico Manuel (2010)
Resonance states of a two-electron quantum dot are studied using a variational expansion with both real basis-set functions and complex scaling methods. We present numerical evidence about the critical behavior of the density of states (DOS) in the region where there are resonances. The critical behavior is signaled by a strong dependence of some features of the DOS on the basis-set size used to calculate it. The resonance energy and lifetime are obtained using the scaling properties of the DOS.